Efficient Optimization of the Performance of Mn2+‐Doped Kesterite Solar Cell: Machine Learning Aided Synthesis of High Efficient Cu2(Mn, Zn)Sn(S, Se)4 Solar Cells (Solar RRL 12∕2018). Issue 12 (6th December 2018) - Li, Xiuling; Hou, Zhufeng; Gao, Shoushuai; Zeng, Yu; Ao, Jianping; Zhou, Zhiqiang; Da, Bo; Liu, Wei; Sun, Yun; Zhang, Yi
Abstract : In article no. 1800198, Bo Da, Yi Zhang, and co‐workers determine the optimal doping content of Mn 2+ in CZTSSe films effectively and rapidly to achieve the best solar cell efficiency by machine learning. A CM0.05 Z0.95 TSSe solar cell with an efficiency of 8.93% is achieved.